1974
DOI: 10.1037/h0036690
|View full text |Cite
|
Sign up to set email alerts
|

Are there two kinds of thinking in process and reactive schizophrenics?

Abstract: A tentative formulation suggesting qualitative differences between process and reactive schizophrenics is presented. The cognitive deficit of reactive schizophrenics is seen as due to fragmentation of relatively normal thinking under stress or during acute disturbance (i.e., on admission). The fragmentation is suggested to result from interference due to excessive responsiveness to external stimuli and task demands. The process schizophrenics are viewed as idiosyncratic (underdeveloped) in thinking with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One way to explore the possible relations between locus of attention deployment, thought familiarity, and hallucinations is to use the premorbid status of the patient as the attentional index. At least three reviews of the schizophrenia literature have concluded that reactive and paranoid schizophrenics tend to deploy their attention so extensively to their external surroundings that they run the risk of stimulus flooding; in contrast, process and nonparanoid schizophrenics restrict their outward attention (DeWolfe, 1974;Silverman, 1964;Venables, 1964). De Wolfe's review is especially germane to the present discussion.…”
mentioning
confidence: 99%
“…One way to explore the possible relations between locus of attention deployment, thought familiarity, and hallucinations is to use the premorbid status of the patient as the attentional index. At least three reviews of the schizophrenia literature have concluded that reactive and paranoid schizophrenics tend to deploy their attention so extensively to their external surroundings that they run the risk of stimulus flooding; in contrast, process and nonparanoid schizophrenics restrict their outward attention (DeWolfe, 1974;Silverman, 1964;Venables, 1964). De Wolfe's review is especially germane to the present discussion.…”
mentioning
confidence: 99%
“…Differences in performance between process and reactive schizophrenics were also expected, with reactive schizophrenics expected to show less deficit than process schizophrenics. This expected difference was based on theory (e.g., Broen, 1968;DeWolfe, 1974) and empirical findings of cognitive differences (e.g., Chapman & Chapman, 1973;Garmezy, 1970;Higgins, 1969), with reactive subjects predicted and usually found to have less deficit. The specific order of deficit from greatest to least for the four groups in the present investigation was predicted to be aphasic, process schizophrenic, reactive schizophrenic, and normal.…”
mentioning
confidence: 95%
“…Several reviews of the literature on schizophrenia (DeWolfe, 1974;Silverman, 1964;Venables, 1964) have concluded that the premorbid status of the patient offers a reliable guide to how the attention is deployed. Reactive (i.e.…”
mentioning
confidence: 99%